Resiliensi Sosial Masyarakat Kampung Mendale Dalam Menghadapi Bencana Banjir Bandang Di Aceh Tengah - Makrifatin Zahra; Ismiati; Zamratul Aini (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Abstract:  The flash floods that struck Mendale Village, Central Aceh Regency, in 2025 caused extensive damage to residential areas and agricultural land while also disrupting the social, economic, and psychological well-being of the community. Although numerous studies have examined community resilience in disaster settings, research specifically focusing on the social resilience of flash flood-affected communities in Mendale Village remains limited. Considering that the village was among the areas most severely affected by the 2025 flash flood, it provides an important context for understanding post-disaster community recovery. This study aims to analyze the impacts of the flash flood, examine the community’s social resilience, and identify the factors that support and hinder the development of social resilience in Mendale Village. This study employed a qualitative approach using a case study design. Ten informants, consisting of disaster-affected residents, village officials, and community leaders, were purposively selected based on their experiences and involvement during the disaster. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model. The findings reveal that the flash flood generated multidimensional physical, social, economic, and psychological impacts. Based on Norris et al.'s framework, community social resilience was developed through four capacities: social capital, community competence, information and communication, and economic development, with social capital emerging as the most dominant capacity. Social resilience was strengthened by social support and spiritual values, whereas economic limitations and geographical conditions hindered the post-disaster recovery process. Keywords: Social recilience, Flash flood, Social capital.